Performance analysis of dw code family for SAC-OCDMA, FTTH network - Kydir, Muthana Yassen (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2011)
The main goal of this research is to evaluate the system performance of OCDMA technique based : i- using MIDW and EDW codes ii- based on RZ and NRZ lines codes iii- based on PIN and APD at the receiver side.